Synthesis of 3,5 Diaryl-4-Aroyl-1-Benzoyl-Δ2-Pyrazolines - K.N. Jaware, Miss; P. Ganorkar, Rajesh; Jamode, V.S. (Asian Journal of Chemistry, 2010)
Some new 3,5-diaryl-4-aroyl-1-benzoyl-Δ2-pyrazolines (3a-p) have been synthesized by the action of benzhydrazide on 3-aroyl flavanones (2a-p) in pyridine medium. Structure of these compounds has been established on the basis of spectral analysis and elemental analysis.